Thermosensitive collagen/fibrinogen gels loaded with decorin suppress lesion site cavitation and promote functional recovery after spinal cord injury - Jacob Matthews (Nature Portfolio, 2021)
Abstract The treatment of spinal cord injury (SCI) is a complex challenge in regenerative medicine, complicated by the low intrinsic capacity of CNS neurons to regenerate their axons and the heterogeneity in size, shape and extent of human injuries. For example, some contusion injuries do not compromise the dura mater and in such cases implantation of preformed scaffolds or drug delivery systems may cause further damage. Injectable in situ thermosensitive scaffolds are therefore a less invasive alternative. In this study, we report the development of a novel, flowable, thermosensitive, injectable drug delivery system comprising bovine collagen (BC) and fibrinogen (FB) that forms a solid BC/FB gel (Gel) immediately upon exposure to physiological conditions and can be used to deliver reparative drugs, such as the naturally occurring anti-inflammatory, anti-scarring agent Decorin, into adult rat spinal cord lesion sites. In dorsal column lesions of adult rats treated with the Gel + Decorin, cavitation was completely suppressed and instead lesion sites became filled with injury-responsive cells and extracellular matrix materials, including collagen and laminin. Decorin increased the intrinsic potential of dorsal root ganglion neurons (DRGN) by increasing their expression of regeneration associated genes (RAGs), enhanced local axon regeneration/sprouting, as evidenced both histologically and by improved electrophysiological, locomotor and sensory function recovery. These results suggest that this drug formulated, injectable hydrogel has the potential to be further studied and translated into the clinic.